2013
DOI: 10.1016/j.conbuildmat.2013.05.101
|View full text |Cite
|
Sign up to set email alerts
|

Reliability-based design optimization of concrete flexural members reinforced with ductile FRP bars

Abstract: Behnam, B., and Eamon, C. (2013). "Reliability-based design optimization of concrete flexural members reinforced with ductile FRP bars." Construction and Building Materials, 47, 942-950, doi: 10.1016Materials, 47, 942-950, doi: 10. /j.conbuildmat.2013 ABSTRACTIn recent years, ductile hybrid FRP (DHFRP) bars have been developed for use as tensile reinforcement. However, initial material costs regain high, and it is difficult to simultaneously meet strength, stiffness, ductility, and reliability demands. In thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…Allen and Maute (2004) combined RBDO and high-fidelity aero elastic simulations of structures. Behnam and Eamon (2013) obtained minimum cost of ductile hybrid fiber reinforced polymer bar configurations by RBDO. Chen et al (2014) developed a cell evolution method for RBDO.…”
Section: Discussionmentioning
confidence: 99%
“…Allen and Maute (2004) combined RBDO and high-fidelity aero elastic simulations of structures. Behnam and Eamon (2013) obtained minimum cost of ductile hybrid fiber reinforced polymer bar configurations by RBDO. Chen et al (2014) developed a cell evolution method for RBDO.…”
Section: Discussionmentioning
confidence: 99%
“…Corrosion of steel in reinforced concrete causes concrete cracking, loss of bond strength, reduction in the steel cross section, and loss of serviceability (Cabrera 1996). It has been reported that the corrosion of steel in reinforced concrete (RC) requires over $8 billion annually for repairing RC bridges in the United States (Behnam and Eamon 2013;US Federal Highway Administration 2001). Although the corrosion of steel in RC may be treated by improving the concrete mix design, increasing the thickness of the concrete cover (Faustino et al 2015), and employing cathodic protection and epoxy-coating methods, such methods fail to completely eliminate the corrosion.…”
Section: Introductionmentioning
confidence: 99%
“…Over the last few decades, the use of FRP as reinforcement in concrete members has gained interest among the researchers and designers owing to the corrosion resistance, high strength and low-weight characteristics of the materials. (Achintha et al 2018;Achintha M 2009;Lou et al 2016Lou et al , 2017ab;Lou and Karavasilis 2018;Sun et al 2017aSun et al , 2018Sun 2018;Sun et al 2016Sun et al , 2017bSun and Ghannoum 2015). Despite FRPs being more expensive than steel on a unit weight basis, it is anticipated that the innovative use of the material together with its long-term benefits such as low maintenance and high durability may enable FRP reinforcement systems to be a viable alternative to steel reinforcement.…”
Section: Introductionmentioning
confidence: 99%
“…Because of their light-weight, high-strength and non-corrosion properties, Fiber Reinforced Polymer (FRP) composites are remarkable materials to strengthen or reinforce concrete structures [1][2][3][4][5][6][7][8][9]. The successful usage of FRP composites to replace steel reinforcements also suggests an over $8 billion annual savings from repairing the corroded components of U.S. bridges [10,11]. However, inadequate deformation resulted from catastrophic brittle failure of FRP rupture limits their vast potentials for structural components.…”
Section: Introductionmentioning
confidence: 99%